2020
DOI: 10.18203/2320-6012.ijrms20203669
|View full text |Cite
|
Sign up to set email alerts
|

Inguinoscrotal swellings in childhood: a clinico-diagnostic approach to differential diagnosis

Abstract: Background: Inguinoscrotal diseases are one of the commonest group of disorders seen in clinical surgical practice. A wide range of swellings are seen in this region in children and includes hydrocele, torsion testis, ectopic testis, lymphadenopathy, inguinal hernias, cysts, epididymitis, orchitis, tumors etc. Vigilant clinical and radiological evaluation of inguinoscrotum for varying diseases helps in proper diagnosis and surgical management of its differential diagnosis.Methods: The present study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…64,65 Although it was known that cisplatin could affect exosome release under non-cytotoxic doses, there has been few quantitative studies on the magnitude of the exosome excretion, which is very important for the drug usage of patients. 64,66 Here, for a quantitative study to assess the effect of the anti-cancer drug, we used the developed biosensor to detect exosome secretion changes for PC-3 cells treated with cisplatin, the first FDA-approved platinum compound for cancer treatment. First, we challenged the biosensor for the direct detection of exosomes in a cell culture supernatant without purification.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…64,65 Although it was known that cisplatin could affect exosome release under non-cytotoxic doses, there has been few quantitative studies on the magnitude of the exosome excretion, which is very important for the drug usage of patients. 64,66 Here, for a quantitative study to assess the effect of the anti-cancer drug, we used the developed biosensor to detect exosome secretion changes for PC-3 cells treated with cisplatin, the first FDA-approved platinum compound for cancer treatment. First, we challenged the biosensor for the direct detection of exosomes in a cell culture supernatant without purification.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ultrasound proves to be a valuable diagnostic tool for identifying subclinical varicosities that may not be apparent during a clinical examination. It also facilitates the assessment of testicular volume, considering the debated association between varicoceles and impaired spermatogenesis, leading to oligozoospermia and infertility [ 16 ]. Furthermore, ultrasound assists in evaluating the kidneys to detect any renal tumours contributing to varicocele development.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred method for assessing metastases is CECT of the chest, abdomen, and pelvis. Wani et al [ 16 ] conducted a study on inguinoscrotal swellings in children, reporting hydrocele as the predominant diagnosis in 31 patients, followed by an inguinal hernia in 14 cases. Vinoth et al [ 17 ] reported a case of unusual inguino-labial swellings in an adult female, highlighting the significance of radiological evaluation in atypical inguino-scrotal/labial swellings.…”
Section: Discussionmentioning
confidence: 99%